2016
DOI: 10.1186/s12971-016-0075-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of tobacco use among adolescents in the schools of Kalaiya, Nepal: a cross-sectional questionnaire based study

Abstract: BackgroundAdolescent students are vulnerable group for tobacco addiction. Tobacco use among school children is becoming a serious problem in developing countries. This study was carried out to estimate the prevalence of tobacco use and to determine associated factors among adolescent students of Kalaiya municipality.MethodsA cross sectional survey was carried out by self-administered questionnaire adapted from Global Youth Tobacco Survey to assess tobacco use among the representative sample of 1540 adolescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 15 publications
8
32
2
Order By: Relevance
“…Pannmasala and Gutkha of various brands which was higher than Kaliaya district of Nepal. 4 More than half tobacco users adolescences obtained tobacco from retail-markets and remaining got from their relatives and friends which was similar to the findings of a study in Dharan of Eastern Nepal. 8 The ever use of tobacco was higher among male students compared to female students which was comparable with the findings of other various studies.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Pannmasala and Gutkha of various brands which was higher than Kaliaya district of Nepal. 4 More than half tobacco users adolescences obtained tobacco from retail-markets and remaining got from their relatives and friends which was similar to the findings of a study in Dharan of Eastern Nepal. 8 The ever use of tobacco was higher among male students compared to female students which was comparable with the findings of other various studies.…”
Section: Discussionsupporting
confidence: 85%
“…Dharan (19.7%), Pokhara (47.1%), Kalaiya (25.3%) and (13.9%) among junior collegiate of western Nepal. 4,8,12,13 The prevalence of smoking among adolescencents was high in African countries i.e. Sierra Leone, Lesotho and Madagascar compared with the findings of this study.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…With regard parental influences on adolescents' smoking habits, the finding in this study concurred with a study among in-school adolescents that revealed students whose family members were tobacco users had higher risk of tobacco use relative to those with no family members using tobacco [25][26][27][28]. It is apparent from this study that good knowledge alone may not result in positive smoking behavior.…”
Section: Discussionsupporting
confidence: 86%